Peningkatan Literasi Keuangan Bagi Kelompok Tani Mandiri di Desa Mudung Darat, Kecamatan Maro Sebo, Kabupaten Muaro Jambi, Sebagai Upaya Penguatan Pengelolaan Usaha Tani - Achmad Hizazi; Dica Lady Silvera; Heriyani Heriyani; Fitrini Mansur; Lutfi Lutfi (Jurnal Pengabdian Masyarakat, 2025)
Low financial literacy and informal bookkeeping constrain the Mandiri Farmer Group’s enterprise management and access to external financing in Mudung Darat, Maro Sebo, Muaro Jambi. This progress report summarizes a three-week participatory mentoring program that strengthened basic financial capabilities, introduced standardized manual and digital cashbooks, and guided the preparation of simple financial statements. Methods combined interactive lectures, simulations, hands-on transaction recording, and coaching using context-fit templates. Early results show the adoption of routine cash recording, the production of the group’s first structured income–expense and simple profit–loss reports, shorter reporting time, and clearer transparency to members. These outputs have begun to inform season-based cost planning and sales decisions, signaling a shift toward data-driven management. The intervention demonstrates that lightweight tools and close mentoring can quickly improve accountability and decision quality in smallholder settings. The approach is scalable for rural groups with similar constraints and supports inclusive, evidence-based agricultural development.